Keragaan Mutan Putatif Purwoceng (Pimpinella pruatjan Molk.) dari Benih Diiradiasi Sinar Gamma pada Tiga Ketinggian Tempat - Wahyu, Yudiwanti; Darwati, Ireng; Rosita, ,; Pulungan, Muhammad Yusuf; Roostika, Ika (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2013)
Pruatjan (Pimpinella pruatjan Molk.) is Indonesian endangered medicinal plant which grows endemically at mountainousarea. To broaden its planting area, an effort to develop low-altitude tolerant genotype of pruatjan had been conductedsince May 2007. Pruatjan seeds harvested from Gunung Putri experimental station (1,545 m asl) were treated with gammairradiation (0-5 krad) and germinated at Gunung Putri. Young seedlings were transplanted into small polybag (Ø 10 cm), anda month later they were moved into 10-kg medium of pot or polybag. Two months later, some of the young plants were moved to Cibadak experimental station (950 m asl) and Cicurug experimental station (550 m asl). All plants were maintained until flowered and produce seeds. The result shows that seeds from all of irradiation level treatments germinated and grew wellalthough the amount of seedlings decreased by the higher level of irradiation treatment. No phenotypic difference of plantsfrom irradiated seed compared with those from non irradiated ones (0 krad). Plants at Cibadak and Cicurug grew faster thanthose at Gunung Putri, and also flowered faster. On April 2008, seeds from 0, 1, 3 and 5 krad treated plant had germinatedat Cicurug, and those seedlings were the candidate genotypes for low-altitude tolerant of pruatjan.Keywords: induced mutation, low altitude tolerant, pruatjan, variability